Homestay Tourism and Sustainable Development in the Indian Himalayan Region: Prospects & Challenges - Raj Sanyal, Prithvi; Kumari, Sunita; Siddiqui, Gulnaz (Management Journal for Advanced Research, 2023)
In developing countries like India, homestay tourism is a relatively a new concept that has been introduced in the field of tourism and travel. It has number of benefits at social, economic and environmental level and simultaneously, it has certain limitations also. Purpose of this research paper is to evaluate the social, economic and environmental issues of homestay in Indian Himalayan Regions so that various tourism policies can be framed. Another purpose is to decide whether homestay is good & safe for an individual as a host and as a guest. Future potentials of home stay tourism has also been highlighted in the present paper and it also carry number of challenges faced by homestay tourism. Some proposed measures to improve homestay tourism have been given. It has been linked with sustainable development also. As per the expectations of the author, the present paper is going to give a lot of ideas & benefits to not only those people who are connected with tourism and travel but it will also give an idea to the govt., environmentalist, young generation, gen-z (specially residing in Himalayan region), spiritual and religious organisations, people interested in knowing the traditions and culture of other regions and to both guest and host community. The focus of the paper is empowering local and rural communities towards homestay tourism and preserving heritage culture of the people residing in Indian Himalayan Regions. Various marketing strategies to promote home stays has also been highlighted in this paper.